Address before the Foreign Policy Association, Cincinnati, Ohio, June 1, 1948 - McCloy, John J. (World Bank, Washington, DC, 2019)
John J. McCloy, President of the International Bank for Reconstruction and Development, spoke about the prospects for success by the European Recovery Program and the role of Bank in it. He commented on the world leadership role of the United States. He reviewed the five loans the Bank has made to date. He concluded by discussing South America countries and their needs for technical assistance and advice in connection with their development.